2023
DOI: 10.3390/bioengineering10050531
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based Identification of Parkinson’s Disease from Continuous Speech in Noisy Environments

Abstract: Parkinson’s disease is a progressive neurodegenerative disorder caused by dopaminergic neuron degeneration. Parkinsonian speech impairment is one of the earliest presentations of the disease and, along with tremor, is suitable for pre-diagnosis. It is defined by hypokinetic dysarthria and accounts for respiratory, phonatory, articulatory, and prosodic manifestations. The topic of this article targets artificial-intelligence-based identification of Parkinson’s disease from continuous speech recorded in a noisy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the remote monitoring of PD using smart devices is gaining popularity, and numerous recent studies have explored the use of mobile devices for voice recording in PD research. For instance, Omberg et al [ 30 ] used an iPhone for their voice recordings, while Farago et al [ 31 ] employed Android smartphone devices (model not specified). On the other hand, Asci et al [ 32 ] utilized various smartphones available on the market (Apple ® , Samsung ® , Huawei ® , Xiaomi ® , and Asus ® ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the remote monitoring of PD using smart devices is gaining popularity, and numerous recent studies have explored the use of mobile devices for voice recording in PD research. For instance, Omberg et al [ 30 ] used an iPhone for their voice recordings, while Farago et al [ 31 ] employed Android smartphone devices (model not specified). On the other hand, Asci et al [ 32 ] utilized various smartphones available on the market (Apple ® , Samsung ® , Huawei ® , Xiaomi ® , and Asus ® ).…”
Section: Methodsmentioning
confidence: 99%
“…Another study employed a MobileNet CNN model with various types of spectrograms as input. The findings indicated that speech energy spectrograms and mel spectrograms yielded the highest accuracy rates of 96% and 92%, respectively [ 31 ]. A study by Khojasteh et al evaluated the performance of a CNN model on sustained vowel phonation recordings of the /a/ lasting over 5 s. When tested on 2 s voice samples segmented into 815 ms frames, the CNNs achieved a classification accuracy of 75.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Speech-Language Pathologists (SLPs) have historically employed voice analysis to diagnose hypokinetic dysarthria, a speech disorder symptomatic of PD. Nonetheless, navigating the subtleties of these changes requires advanced analytical capabilities beyond conventional statistical approaches (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%